Alkenylated phenolics from Syzygium lineatum with antiproliferative activity against chronic myeloid leukemia cells - Franklin V. Ibana, Von Novi O. de Leon, Joe Anthony H. Manzano, Agnes L. Castillo, Allan Patrick G. Macabeo (Journal of Applied Pharmaceutical Science, 2024)
Syzygium lineatum is traditionally used by Filipinos as an anticancer regimen and food flavouring in the Philippines. However, its medicinal potential is yet to be validated. Herein, we report the antiproliferative and cytotoxic activities of S. lineatum extracts, sub-extracts, and alkenylated phenolic constituents gingkol (1) and bilobol (2) along with β-sitosterol (3) and a mixture of fatty acids (4–6) in vitro and in silico. Fractions 2 and 4 (SlPE4) from the biologically active petroleum ether sub-extract (SlPE), showed moderately strong antiproliferative activity against chronic myeloid leukemia (CML) cells (K-562). Chromatographic purification of fraction SlPE4 yielded antiproliferative compounds 1 and 2 against K-562 cells while SlPE2 afforded 3–6. Bilobol (2), an alkenylated resorcinol, showed better selectivity in vitro compared to the phenolic congener, gingkol (1) highlighting the importance of increased hydroxylation in the aromatic structure of the compounds. To elucidate their putative mechanisms of action, molecular docking studies were performed versus establishing the CML targets BCR::ABL1 tyrosine kinase, c-Src kinase, and protein kinase B. In silico results showed moderate to good binding affinities of 1 and 2 in the active sites of the target kinases. Overall, the study validates the purported Philippine traditional anticancer use of S. lineatum, especially its constituents gingkol (1) and bilobol (2).
Keywords: Syzygium lineatum, anticancer, chronic myeloid leukemia cells, molecular docking, gingkol, bilobol